2009
DOI: 10.1186/1475-2875-8-207
|View full text |Cite
|
Sign up to set email alerts
|

The neurological assessment in young children treated with artesunate monotherapy or artesunate-mefloquine combination therapy for uncomplicated Plasmodium falciparum malaria

Abstract: The neurological assessment in young children treated with artesunate monotherapy or artesunate-mefloquine combination therapy for uncomplicated Plasmodium falciparum malaria AbstractBackground: Mefloquine and artesunate combination therapy is the recommended first-line treatment for uncomplicated malaria throughout much of south-east Asia. Concerns have been raised about the potential central nervous system (CNS) effects of both drug components and there are no detailed reports in very young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“… 37 In a recent study, neither artesunate nor mefloquine resulted in significant impairment of behavior or motor function in Karen children, aged between 3 months and 5 years, when compared with non-febrile controls. 38 Our study in young African children confirmed these findings. We observed a low incidence of neuropsychiatric AEs; none represented a safety concern.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“… 37 In a recent study, neither artesunate nor mefloquine resulted in significant impairment of behavior or motor function in Karen children, aged between 3 months and 5 years, when compared with non-febrile controls. 38 Our study in young African children confirmed these findings. We observed a low incidence of neuropsychiatric AEs; none represented a safety concern.…”
Section: Discussionsupporting
confidence: 85%
“…One study performed in Southeast Asia found no evidence for such effects in children less than 5 years of age (weighing > 5 kg), when mefloquine, either alone or combined with an artemisinin derivative, was administered to treat falciparum or vivax malaria 37. In a recent study, neither artesunate nor mefloquine resulted in significant impairment of behavior or motor function in Karen children, aged between 3 months and 5 years, when compared with non-febrile controls 38. Our study in young African children confirmed these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, late onset neurological and neuropsychiatric adverse events were recorded in contrast to the study by Ambler et al [2]. Hyperactivity, as the only neuropsychiatric adverse event (0.5%), was detected after day 28.…”
Section: Discussionmentioning
confidence: 58%
“…Relevant neuropsychiatric adverse events are difficult to identify in young children and are consequently under-reported. Another study of artesunate–mefloquine (fixed dose of 50 mg artesunate and 125 mg mefloquine per day for 3 days) in 213 young children in Africa, 28 with a 63-day follow-up, actively tested for neuropsychiatric effects (using standard infant neurological tests) and reported mild-to-moderate, spontaneously resolving neuropsychiatric adverse events, with sleeping disorders being the most common (2·3% of patients). Notably, because of the risk of serious psychiatric side-effects, the latest WHO antimalarial treatment guideline 3 recommends an interval of 60 days between consecutive periods of mefloquine treatment.…”
Section: Discussionmentioning
confidence: 99%